Differences in injury incidence between player positions across all rugby formats - a systematic review and meta-analysis - Vaajala, M.; Laaksonen, J.; Liukkonen, R.; Pakarinen, O.; Kuitunen, I. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Rugby is a high-intensity contact sport with a high incidence of injuries. The aim of this systematic review and meta-analysis was to compare the injury incidences between forwards and backs in all rugby formats (Rugby Union, Seven, and League). The PubMed (National Library of Medicine), Web of Science (Clarivate), Scopus (Elsevier), and SPORTDiscus (EBSCO) databases were searched from inception to October 10, 2024. A study was eligible if the number of rugby injuries per exposure time for backs and forwards was reported. Incidence rate ratios (IRRs) with 95% confidence intervals (CI) were compared between forwards and backs. After screening 1514 studies, a total of 49 studies were included. The total exposure time was 902 280 player-hours for backs and 1 127 610 player-hours for forwards. Forwards had a slightly higher incidence of injuries in Rugby Union (IRR 1.03, CI 1.00-1.06) and Rugby League (IRR 1.31, CI 1.23-1.41). However, forwards had a lower overall incidence of injuries in Rugby Sevens (pooled IRR 0.78, CI 0.73-0.85). Strain injuries and injuries caused by tackling, running, or collision were more common in backs across rugby formats. In addition to a more standardized definition of injuries and more comprehensive subgroup analyses in future studies, different trends and patterns in injury occurrence regarding playing positions in all rugby formats should be further studied to develop more targeted injury prevention strategies in forwards and backs.